Media Video Tutorial untuk Meningkatkan Hasil Belajar Peserta Diklat Jarak Jauh Multimedia Bagi Guru - Wiwin Sunarsi Tubagus (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2020)
This study aims to see the effect of instructional video media in improving the learning outcomes of multimedia distance training participants for teachers. The population and sample in this study were participants of the Multimedia Distance Training for Teachers, 40 participants. The method used in this research is quantitative description. From the analysis and calculations that have been carried out, it is obtained with a confidence level of 95%, it turns out that tcount> t table, namely 2.371> 2.022. This means that there is a significant difference between the results before and after the learning process using video media for the participants of the Multimedia Distance Training for Teachers. This shows that the learning technique using learning video is effective, because it can improve the ability of participants to obtain learning outcomes. The participants can continue to listen to the video tutorials that have been given, so that the participants' understanding of the material given can increase.